An evaluation of teachers' performance on gender and work experience with the charlotte danielson evaluation model - Lelatobur, Lovely Ezverenzha; Manongga, Daniel Herman Ferdy; Iriani, Ade (Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
The performance teachers in the preliminary study still use teacher-centred methods, both teachers who have received certification and those who have not. On the other hand, the evaluation in schools is still on teacher performance related to learning design and the learning process in the class. Therefore, social, personality and professional competencies are still less reviewed. The purpose of this study is to evaluate teachers' performance based on their gender and work experience in public senior high schools in Maluku Barat Daya (MBD) district. Four main components were used to assess teacher performance: lesson planning and preparation, class management, lesson implementation, and professional responsibility. Data was collected from twelve teachers using the Charlotte Danielson Evaluation Model. Simple qualitative and quantitative approaches were used to collect data. The results showed that both female and male teachers planned and designed lessons well. In class management, female teachers performed very well, while male teachers performed well. In implementation, female teachers performed very well, while male teachers were categorized as good. Professional responsibility was evaluated as good for both gender groups. The study also showed that gender affects class management and implementation performance, while work experience has no significant effect.